2002
DOI: 10.1074/jbc.m201100200
|View full text |Cite
|
Sign up to set email alerts
|

The EIIIA Segment of Fibronectin Is a Ligand for Integrins α9β1 and α4β1Providing a Novel Mechanism for Regulating Cell Adhesion by Alternative Splicing

Abstract: Although it has been clear for many years that fibronectin (FN) 1 is alternatively spliced, the functions of, and receptors for, two alternatively spliced segments termed EIIIA (or ED-A) and EIIIB (or ED-B) segments have remained elusive. More is known about a non-homologous IIICS repeat encoding the CS-1 segment, which is a cell adhesive site and ligand for integrin ␣ 4 ␤ 1 (1). Both the EIIIA and EIIIB segments are homologous FN type III repeats and are prominently expressed during embryogenesis; homozygou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
167
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(175 citation statements)
references
References 56 publications
6
167
0
2
Order By: Relevance
“…This motif has been shown to promote cell adhesion by interacting with ␣ 4 ␤ 1 and ␣ 4 ␤ 7 integrins (26). Therefore, this newly synthesized FN (EDIϩ, IIICS-120) would have an enhanced potential for binding to a specific subset of integrins associated with cell adhesion, proliferation, migration, and matrix metalloproteinase induction (4,6,(27)(28)(29). Conversely, the EDIIϩ FN isoform was not detected in RNA from untreated cells, and none of the described stimuli altered this splicing pattern (Fig.…”
Section: Differential Regulation Of Fn Alternatively Spliced Exons Inmentioning
confidence: 89%
See 1 more Smart Citation
“…This motif has been shown to promote cell adhesion by interacting with ␣ 4 ␤ 1 and ␣ 4 ␤ 7 integrins (26). Therefore, this newly synthesized FN (EDIϩ, IIICS-120) would have an enhanced potential for binding to a specific subset of integrins associated with cell adhesion, proliferation, migration, and matrix metalloproteinase induction (4,6,(27)(28)(29). Conversely, the EDIIϩ FN isoform was not detected in RNA from untreated cells, and none of the described stimuli altered this splicing pattern (Fig.…”
Section: Differential Regulation Of Fn Alternatively Spliced Exons Inmentioning
confidence: 89%
“…FN is the ligand for at least a dozen members of the integrin receptor family. EDI itself binds to ␣ 4 ␤ 1 and ␣ 9 ␤ 1 (29), and IIICS contains binding sites for ␣ 4 ␤ 1 and ␣ 4 ␤ 7 (47). Recently, a novel glycosaminoglycan-binding site has been identified within the FN IIICS, showing that cooperation between cell surface proteoglycans and integrins is important for mediating the adhesion of cells to FN (48).…”
mentioning
confidence: 99%
“…FAK is also an important regulator of cell survival signalling [13]. Apoptosis induced by loss of adhesion or adhesion-mediated signalling (termed "anoikis") is associated with deactivation of FAK [14,15]. A role of FAKmediated signals in mesenchymal cell survival has been demonstrated in studies showing that fibroblasts in contractile gels are protected from apoptosis by activating antibodies to α5β1 integrins or through constitutive activation of FAK [16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, adhesion of cells expressing either ␣9␤1 or ␣4␤1 was reduced when cultured on two of the shorter deletion mutants with intact C-CЈ loop of EIIIA (EIIIA-(24 -66) and EIIIA- (30 -57)). These data suggested that the optimal ligand binding site for ␣9␤1 and ␣4␤1 in the EIIIA segment could require both the C-CЈ loop and additional flanking sequences (1). In addition, mAbs IST-9 or 3E2 inhibited ␣9-and ␣4-mediated cell adhesion to the EIIIA segment, suggesting that the ligand binding site includes the C-CЈ loop (1).…”
mentioning
confidence: 97%
“…Cell Culture-SW480, two human colon carcinoma cell lines, stably transfected with either integrin ␣9 or vector alone, were maintained in Dulbecco's modified Eagle's medium (DMEM) (Invitrogen) supplemented with 10% fetal bovine serum (HyClone, Logan, UT), 1% penicillin and streptomycin, and 2% Geneticin (Invitrogen) as described previously (1,47). Cells were incubated in a humidified incubator (Thermo Electron Corp., Waltham, MA) at 37°C in 5% CO 2 .…”
Section: Ltd)mentioning
confidence: 99%